2009
DOI: 10.1112/s0010437x09004023
|View full text |Cite
|
Sign up to set email alerts
|

Noncrossing partitions and representations of quivers

Abstract: We situate the noncrossing partitions associated with a finite Coxeter group within the context of the representation theory of quivers. We describe Reading's bijection between noncrossing partitions and clusters in this context, and show that it extends to the extended Dynkin case. Our setup also yields a new proof that the noncrossing partitions associated with a finite Coxeter group form a lattice. We also prove some new results within the theory of quiver representations. We show that the finitely generate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
169
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 149 publications
(176 citation statements)
references
References 34 publications
5
169
0
2
Order By: Relevance
“…In [19], two of the authors of the present paper showed that when Q is Dynkin, any abelian and extension-closed subcategory arises as the θ-semi-stable subcategory of a suitable choice of θ. In fact, somewhat more is known; see [19,Theorem 1.1].…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…In [19], two of the authors of the present paper showed that when Q is Dynkin, any abelian and extension-closed subcategory arises as the θ-semi-stable subcategory of a suitable choice of θ. In fact, somewhat more is known; see [19,Theorem 1.1].…”
Section: Introductionmentioning
confidence: 76%
“…In Dynkin type, the semi-stable subcategories (or equivalently the abelian and extension-closed subcategories) form a lattice. It was shown in [19] that this poset is isomorphic to the lattice of noncrossing partitions associated to the Weyl group corresponding to Q. These lattices had already been studied by combinatorialists and group theorists and, especially relevant for our purposes, they play a central role in the construction of the dual Garside structure of Bessis [3] on the corresponding Artin group, which also leads to their use in constructing Eilenberg-Mac Lane spaces for the Artin groups [4,5].…”
Section: Theorem 55 For Q a Euclidean Quiver An Abelian And Extensmentioning
confidence: 99%
See 1 more Smart Citation
“…These notions were already studied by Auslander and Smalø [9] in the 1980's, but we are using here the terminology adopted by Adachi, Iyama and Reiten in [2], which generalises the work of Ingalls and Thomas [52] on hereditary algebras.…”
mentioning
confidence: 99%
“…Following Ingalls-Thomas [9], the cone S(Q) of finite stability conditions is, by definition, the set of all σ ∈ Q Q 0 for which there are finitely many, up to isomorphism, σ-stable representations.…”
Section: Introductionmentioning
confidence: 99%